Armenian, Hittite, and Indo-European studies: a commemoration volume for Jos J.S. Weitenberg - Bläsing, Uwe; Dum-Tragut, Jasmine; Lint, Theo Maarten van (Hebrew University Armenian studies, 2019)
Jos J.S. Weitenberg, Professor of Armenian Studies at Leiden University (1994-2009), co-founder and President of the Association Internationale des Études Arméniennes, was a scholar of global standing in Hittite, Armenian and Indo-European linguistics. The twenty-three studies by colleagues and former students gathered in this volume reflect some of the depth and breadth of Weitenberg's scholarship: Hittite and Anatolian, to which Weitenberg made a classic contribution with 'Die hethitischen u-Stämme' (1984), and Indo-European etymologies. Armenian dialectology is well represented, as are contributions to wider Armenian culture, and the reception of Greek literary culture in Armenian. Further studies are devoted to digital preparation of critical editions, the relationship between master and pupil as well as the Armenian reception and interpretation of Biblical and apocryphal material, to which Weitenberg contributed in 'Eusèbe d'Émèse. Commentaire de la Genèse. Texte arménien de l'édition de Venise [1980]. Fragments grecs et syriaques. Avec traductions', together with Françoise Petit and Lucas Van Rompay (2011)
Literaturverzeichnis: Seite 439-498. - Index
Literaturverzeichnis Jos J.S. Weitenberg: Seite XIII-XXVI
Keywords: Festschrift; Aufsatzsammlung; Armenische Apostolische Kirche; Indogermanische Sprachen; Armenisch